Early life stress increases vulnerability to the sequelae of pediatric mild traumatic brain injury - Diaz-Chávez, Arturo (Exp Neurol, 2020)
Early life stress (ELS) is a risk factor for many psychopathologies that happen later in life. Although stress can occur in cases of child abuse, studies on non-accidental brain injuries in pediatric populations do not consider the possible increase in vulnerability caused by ELS. Hence, we sought to determine whether ELS increases the effects of pediatric mild traumatic brain injury (mTBI) on cognition, hippocampal inflammation, and plasticity. Male rats were subjected to maternal separation for 180 min per day (MS180) or used as controls (CONT) during the first 21 post-natal (P) days. At P21 the rats were anesthetized with isoflurane and subjected to a mild controlled cortical impact or sham injury. At P32 the rats were injected with the cell proliferation marker bromodeoxyuridine (BrdU, 500 mg/kg), then evaluated for spatial learning and memory in a water maze (P35–40) and sacrificed for quantification of Ki67(+), BrdU(+) and Iba1(+) (P42). Neither MS180 nor mTBI impacted cognitive outcome when provided alone but their combination (MS180 + mTBI) decreased spatial learning and memory relative to Sham controls (p< 0.01). mTBI increased microglial activation and affected BrdU(+) cell survival in the ipsilateral hippocampus without affecting proliferation rates. However, only MS180 + mTBI increased microglial activation in the area adjacent to the injury and the contralateral CA1 hippocampal subfield and decreased cell proliferation in the ipsilateral neurogenic niche. Overall, the data show that ELS increases the vulnerability to the sequelae of pediatric mTBI and may be mediated by increased neuroinflammation.